A newly discovered Greek Father : Cassian the Sabaite eclipsed by John Cassian of Marseilles - Cassian, the Sabaite, approximately 470-548. (Vigiliae Christianae, Supplements, 2012)
This is a critical edition of texts of Codex 573 (ninth century, Monastery of Metamorphosis, Meteora, Greece), which are published along with the monograph identifying The Real Cassian , in the same series. They cast light on Cassian the Sabaite, a sixth century highly erudite intellectual, whom Medieval forgery replaced with John Cassian. The texts are of high philological, theological, and philosophical value, heavily pregnant with notions characteristic of eminent Greek Fathers, especially Gregory of Nyssa. They are couched in a distinctly technical Greek language, which has a meaningful record in Eastern patrimony, but mostly makes no sense in Latin, which is impossible to have been their original language. The Latin texts currently attributed to John Cassian, the Scythian of Marseilles, are heavily interpolated translations of this Greek original by Cassian the Sabaite, native of Scythopolis, who is identified with Pseudo-Caesarius and the author of Pseudo Didymus' De Trinitate . Codex 573, entitled The Book of Monk Cassian , preserves also the sole extant manuscript of the Scholia in Apocalypsin, the chain of comments that were falsely attributed to Origen a century ago. A critical edition of these Scholia has been published in a separate edition volume, with commentary and an English translation (Cambridge).